2010
DOI: 10.1016/j.neuropharm.2009.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor prevents phencyclidine-induced apoptosis in developing brain by parallel activation of both the ERK and PI-3K/Akt pathways

Abstract: SummaryPhencyclidine is an N-methyl D-aspartate receptor (NMDAR) blocker that has been reported to induce neuronal apoptosis during development and schizophrenia-like behaviors in rats later in life. Brain derived neurotrophic factor (BDNF) has been shown to prevent neuronal death caused by NMDAR blockade, but the precise mechanism is unknown. This study examined the role of the phosphatidylinositol-3 kinase (PI3K)/Akt and extracellular signal-regulated kinase (ERK) pathways in BDNF protection of PCP-induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 42 publications
(60 reference statements)
2
31
0
Order By: Relevance
“…Our aim was to evaluate and compare if the efficiency of bound BDNF is similar to free BDNF. Since BDNF has been shown to prevent apoptosis in different cells including brain cells [31], we wanted to check the efficiency of nanofurmulation by evaluating its ability to suppress apoptosis induced by morphinein PBMC. As expected, morphine (10 −7 M) induced apoptosis (55%) in PBMC compared to untreated cells (p = 0.006) as shown in figure 3A.…”
Section: Resultsmentioning
confidence: 99%
“…Our aim was to evaluate and compare if the efficiency of bound BDNF is similar to free BDNF. Since BDNF has been shown to prevent apoptosis in different cells including brain cells [31], we wanted to check the efficiency of nanofurmulation by evaluating its ability to suppress apoptosis induced by morphinein PBMC. As expected, morphine (10 −7 M) induced apoptosis (55%) in PBMC compared to untreated cells (p = 0.006) as shown in figure 3A.…”
Section: Resultsmentioning
confidence: 99%
“…Once activated, it phosphorylates CREB (33), which in turn, switches on the expression of BDNF (34). Conversely, BDNF per se phosphorylates AKT and CREB to promote cell survival against the insults (35). In support, all of AKT, CREB, and BDNF have shown to suppress the activation of caspase 3 and the occurrence of apoptotic death in various pathologic conditions (36-38).…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that multiple molecular pathways are involved, including the mTORC1, PI 3-kinase and MAP-kinase pathways. These are also downstream of brain-derived neurotrophic factor (Chen et al, 2009; Xia et al, 2010), which has been shown to induce cholesterol synthesis and synapse development in primary cultured neurons (Suzuki et al, 2007). Insulin action on GSK3β and other pathways has also been shown to play a role in controlling Tau phosphorylation in the CNS (Lucas et al, 2001; Schubert et al, 2004) and neural progenitor homeostasis (Kim et al, 2009).…”
Section: Discussionmentioning
confidence: 99%